Activity of agroholdings in the world market of agricultural products in the context of globalization - Babenko, Vitalina; Sidorov, Vadim; Savin, Ruslan (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2019)
Modern processes of reforming the agroindustrial complex of Ukraine in the conditions of globalization of world economic processes in the agricultural market requires from the domestic agroholdings the improvement and rational management of production activity. So the tendencies of development of agroholdings and other agroformations in modern socio-economic conditions are relevant. In order to study the mechanism of their development, models of interconnection between the components of production of the main types of products of agricultural holdings and the availability of agricultural raw materials are constructed. The main approaches are the multivariate regression modeling of the dependence of production of agricultural holdings on components of agricultural production. The subject of the study in the article is the development of the agroholdings. The goal is researching of the tendencies of development of agroholdings and other agroformations in modern socio-economic conditions. Objectives: research of dynamics of the development of agroholdings of Ukraine in terms of its components in the conditions of globalization of world economic processes in the market of agricultural products. Common scientific methods are used: system analysis for to determine the peculiarities of the development of the agro-industrial production in Ukraine; the regression analysis for calculating of the dependence of production of agricultural holdings on components of agricultural production. The following results: on the basis of the analysis of the dynamics of changes in the main indices of domestic agricultural production were obtained analytical interdependence of factors influencing on development of agroholdings. Conclusions: the multivariate regression model of the dependence of production of agricultural holdings on components of agricultural production is calculated; obtained researchings are expedient to use in foreign economic activity as recommendations for definition of the strategy of Ukraine on the world market of agricultural products.